The Peroxisomal 3-keto-acyl-CoA thiolase B Gene Expression Is under the Dual Control of PPARα and HNF4α in the Liver. (15th December 2010) - Chamouton, J.; Hansmannel, F.; Bonzo, J. A.; Clémencet, M. C.; Chevillard, G.; Battle, M.; Martin, P.; Pineau, T.; Duncan, S.; Gonzalez, F. J.; Latruffe, N.; Mandard, S.; et al.
Abstract : PPAR α and HNF4 α are nuclear receptors that control gene transcription by direct binding to specific nucleotide sequences. Using transgenic mice deficient for either PPAR α or HNF4 α, we show that the expression of the peroxisomal 3-keto-acyl-CoA thiolase B ( Thb ) is under the dependence of these two transcription factors. Transactivation and gel shift experiments identified a novel PPAR response element within intron 3 of the Thb gene, by which PPAR α but not HNF4 α transactivates. Intriguingly, we found that HNF4 α enhanced PPAR α /RXR α transactivation from TB PPRE3 in a DNA-binding independent manner. Coimmunoprecipitation assays supported the hypothesis that HNF4 α was physically interacting with RXR α . RT-PCR performed with RNA from liver-specific HNF4 α -null mice confirmed the involvement of HNF4 α in the PPAR α -regulated induction of Thb by Wy14, 643. Overall, we conclude that HNF4 α enhances the PPAR α -mediated activation of Thb gene expression in part through interaction with the obligate PPAR α partner, RXR α .